ANALISIS KERAPUHAN STRUKTUR GEDUNG GSL UNMER MADIUN DENGAN PUSHOVER ANALYSIS - Rohman, Rosyid Kholilur; Afrianto, Arif; Wibowo, Rendi Gusta (Jurnal Teknik Sipil dan Arsitektur, 2025)
This study examines the fragility curve of the GSL building of Merdeka University of Madiun which was built around 1995 with reference to the SNI 1726:1989 standard. This building is an educational building with a structure using reinforced concrete. Modeling and structural analysis using ETABS software. Loading refers to SNI 1727 2020 and SNI 1726 2019. The analysis was carried out using the pushover analysis method referring to ATC-40. The fragility curve developed describes the probability of damage at various levels of Spectral Displacement (Sd). From this study, the base shear due to earthquake force was 4214 kN. The maximum value of base shear was 7890 kN and the maximum displacement of 0.359 m. Based on the conversion results obtained Sd at performance point 0.082 m, the probability for slight damage limits is 95%, moderate 78%, extensive 70%, and complete 45%. This research provides a basis for structural retrofit planning to increase the structural capacity of buildings due to earthquake load